Synthesis and Characterization of Polyurethane Coatings derived from Polyols Synthesized with Glycerol, Phthalic Anhydride and Oleic Acid - Velayutham, T.S.; Majid, W.H.; Ahmad, A.B.; Kang, G.Y.; Gan, S.N. (2009)
Polyester polyols, with various oleic acid contents were used in the preparation of polyurethane (PUR) coatings. The polyols were designated as Alk28, Alk40 and Alk65, in which 28,40 and 65 represents the percentages of oleic acid in the respective formulations. The physical properties of the polyols such as acid value and hydroxyl value have been determined and the infrared (IR) spectroscopic analysis of the polyols is reported. The polyols were reacted with aromatic isocyanate (toluene 2,4-diisocyanate, TDI) to form PUR coatings. The effects of varied NCO/OH ratio and oleic acid content of polyols on physical properties of PUR coatings on mild steel panel were determined. The characterization of PUR coatings carried out by IR spectroscopic analysis and physico-chemical properties such as drying time, pencil hardness, adhesion properties, solvent resistance and corrosion/chemical resistant determination were reported. The coatings obtained from polyol Alk28, exhibits the best overall properties followed by Alk40. PUR coatings from Alk65 were softer. As the NCO/OH ratio of the coatings increased, there were progressive increases in mechanical and anticorrosive properties for all the coatings. Overall, these studies showed that the material holds promise for use as effective surface coating compound by designing the formulation of the desired performance. (C) 2009 Elsevier B.V. All rights reserved.